The influence of guided sleeve height, drilling distance, and drilling key length on the accuracy of static Computer‐Assisted Implant Surgery. (27th December 2018) - El Kholy, Karim; Janner, Simone F. M.; Schimmel, Martin; Buser, Daniel
Abstract: Objective: The aim of this study was to evaluate the effect of guided sleeve height, drilling distance, and guided key height on accuracy of static Computer‐Assisted Implant Surgery (sCAIS). Materials and Methods: Pre and post‐operative positions of implants placed in duplicate dental models were compared and recorded after placement of implants according to a standardized treatment planning and execution sCAIS protocol. Guided sleeve heights: 2 mm, 4 mm, 6 mm and guided key heights: 1 mm and 3 mm were equally randomized in six test groups with varying implant lengths (10‐16 mm) and surgical drilling protocols. The mean crestal and apical three‐dimensional (3D) deviation, as well as the angular deviation were calculated for each group. Data was analyzed using multivariate analysisanova . P values less than .05 were considered statistically significant. All P values of post‐hoc tests were corrected for multiple testing using Bonferroni‐Holm's adjustment method. Results: 3D implant positioning accuracy was not significantly affected by the difference in sleeve height alone or by the implant length alone ( P > .05). However, 3D and angular deviation values became significantly higher as the total drilling distance below the guided sleeve increased and significantly became lower as the guided key height above the sleeve increased. 18 mm drilling distance resulted in a significantly higher deviation, when compared to 14 mm or 16 mm drilling distances, irrespective of sleeve height or implant length ( P < .01). 3 mm key height resulted in significantly less 3D deviation than 1 mm key height ( P < .01). Conclusion: Decreasing the drilling distance below the guided sleeve, by using shorter sleeve heights or shorter implants can significantly increase the accuracy of sCAIS.